Expanding the Horizon of Mechanochromic Detection by Luminescent Shear Stress Sensor Supraparticles - Wintzheimer, Susanne; Reichstein, Jakob; Wenderoth, Sarah; Hasselmann, Sebastian; Oppmann, Maximilian; Seuffert, Marcel T.; Mueller-Buschbaum, Klaus; Mandel, Karl (Advanced Functional Materials, 2019)
Novel sensor particles have been developed that expand the variety of today's mechanochromic systems. The developed supraparticles consist of several different components to enable the sensor function. First, a luminescence-quenching core material is coated with silica nanoparticles. Second, this structure is surrounded by raspberry-like nanostructured silica particles, which host luminophore moieties. Upon shear stress, components spatially separated in the original supraparticles, namely quencher and luminophore components, come into contact. This causes an irreversible quenching of the luminescence (sensor turn-off). Different options to select core, quencher, and luminophore components allow to drive the sensors to different sensing options regarding response time, sensitivity, and operation time. The sensors can be sensitive and rapid in response or generated to monitor the influence of shear stress over longer periods of time. Thus, a rapid, visible, “on-the-fly” sensing of shear stress is possible as well as monitoring the impact of prolonged shear stress. The particles are assembled by spray-drying. This affords flexibility when choosing the type of quencher and luminophore moiety. As such, the sensitivity of this robust, particle-based shear stress sensor system can be deliberately configured. Furthermore, the supraparticle sensor can be integrated in surfaces to create interactive, communicating materials.
CRIS-Team Scopus Importer:2020-04-02
Keywords: luminescence; mechanochromic; sensor; shear stress; supraparticles